Through murky waters: conservation implications from evaluating the drivers of diversity and abundance on coral reef communities in Cambodia - Fiona Chong; Morokot Long; Stéphane De Palmas; Sorn Srenh; Stefanie M. Rog; Matthew Glue; Ouk Vibol; James Davis Reimer (Biodiversity and Conservation, 2026)
Cambodia’s coral reefs are vital for supporting marine biodiversity and coastal livelihoods, but they remain understudied and are increasingly threatened by overfishing, habitat degradation, and climate change. Using Reef Check citizen science data from 91 reef sites (2021–2023), we examined how turbidity and productivity, sea surface temperature (SST), hard coral cover and marine protected area (MPA) designation shape coral reef communities across nearshore and offshore reefs. Our analyses revealed distinct benthic, fish, and invertebrate communities nearshore and offshore. Offshore reefs, characterized by lower turbidity and dominated by branching corals, hosted more fusiliers (Caesionidae) and wrasses (Labridae), and had higher abundances of fish and invertebrates. Nearshore turbid reefs dominated by massive and encrusting corals exhibited higher invertebrate diversity despite lower fish and invertebrate abundance. Hard coral cover increased fish abundance and biomass. Warmer SSTs were associated with reduced fish diversity. Reefs within the Koh Rong Marine National Park did not have higher fish or invertebrate diversity, abundance or targeted fish biomass than outside the MPA, which may reflect mixed zoning, site selection history and enforcement limitation. Our findings showcase the contemporary status of Cambodian reefs, and the potential of citizen science to support baseline monitoring. We recommend expanding MPAs to connect offshore and nearshore reefs while accounting for fishing pressure and enforcement capacity. We also show that integrating satellite data with citizen monitoring can aid adaptive marine conservation planning.

Modelling Asparagopsis nitrogen bioremediation efficiency in Australian coastal environments - Tormey Reimer; Katherine A. Cresswell; Kate M. Fraser; Camille A. White; Scott A. Hadley (Ecological Modelling, 2026)

Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Relative effectiveness of high-dose versus standard-dose influenza vaccine against hospitalizations and mortality according to Charlson Comorbidity Index: A post-hoc analysis of the DANFLU-1 randomized trial - Katrine Feldballe Bernholm; Niklas Dyrby Johansen; Caroline Espersen; Daniel Modin; Kira Janstrup Hyldekær; Joshua Nealon; Sandrine Samson; Matthew M. Loiacono; Rebecca C. Harris; Carsten Schade Larsen; Anne Marie Reimer Jensen; Nino Emanuel Landler; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose The DANFLU-1 trial suggested lower incidence of hospitalizations for pneumonia and influenza, respiratory disease and all-cause mortality among older adults receiving high-dose (HD-IV) versus standard-dose (SD-IV) influenza vaccine. This study assessed the relative effectiveness of HD-IV versus SD-IV according to comorbidity in elderly individuals. Methods This was a post-hoc analysis of the DANFLU-1 randomized controlled feasibility trial of HD-IV versus SD-IV conducted during the 2021–2022 influenza season in adults aged 65–79 years. Outcomes assessed included influenza-related, respiratory, and cardiovascular hospitalizations, and mortality. We tested for effect modification by level of the Charlson Comorbidity Index (CCI) using ICD-10 codes up to 10 years prior to randomization. Results Of the 12,477 randomly assigned participants (mean age 71.7 ± 3.9 years, 47.1% female), 8,020 (64.3%) had CCI = 0, 3,560 (28.5%) had CCI = 1–2 and 893 (7.2%) had CCI ≥ 3. When comparing HD-IV with SD-IV, hazard ratios of hospitalizations for pneumonia and influenza were similar across CCI groups (HR [95%CI]: 0.15 [0.03–0.68] for CCI = 0, 0.36 [0.11–1.15] for CCI = 1–2, 1.00 [0.25-4.00] for CCI ≥ 3). Comparable patterns were found for hospitalizations for respiratory disease (0.46 [0.17–1.20] for CCI = 0, 0.67 [0.32–1.39] for CCI = 1–2, 0.66 [0.24–1.87] for CCI ≥ 3) and all-cause mortality (0.28 [0.09–0.86] for CCI = 0, 0.70 [0.30–1.63] for CCI = 1–2, 0.57 [0.24–1.36] for CCI ≥ 3). There was no statistical evidence of effect modification by CCI for any outcome. Conclusions The lower incidences of clinical outcomes for HD-IV compared to SD-IV were not significantly modified by CCI. The potential benefit of HD-IV versus SD-IV may therefore be applicable regardless of comorbidity burden. Further research is required to confirm these findings.

Antibacterial marinopyrroles and pseudilins act as protonophores - Chambers C. Hughes; Gabriel Castro-Falcón; Jan Straetener; Jan Bornikoel; Daniela Reimer; Trevor N. Purdy; Anne Berscheid; Florence M. Schempp; Dennis Y. Liu; Roger G. Linington; Heike Brötz-Oesterhelt (Phytochemistry Letters, 2025)

Microhabitat associations and benthic community structure of Nanipora (Helioporidae) across the western Pacific - Guillermo M. Castelló; Dan Ishibashi; Jue Alef A. Lalas; Iori Mizukami; Mackenzie L. B. Stoeltje; Meng C. Li; Hsiang-Lun Huang; Keryea Soong; James Davis Reimer (Marine Biodiversity, 2025)

Use of recycled phosphorus products in organic farming in EU member states: Theoretically supported but practically restricted - S. Magaya; M. Reimer; G.S. Metson; T-S. Neset; M. Torralba; C.J.E. Schulp (Food Policy, 2025)

Lunar cycle effects on pelagic predators and fisheries: insights into tuna, billfish, sharks, and rays - Samantha Andrzejaczek; Alexandra E. DiGiacomo; Chloe S. Mikles; Camille M. L. S. Pagniello; Theodore E. J. Reimer; Barbara A. Block (Reviews in Fish Biology and Fisheries, 2025)

Exploring species and functional diversity of fishes in Cambodian coastal habitats using eDNA metabarcoding - Charlotte G. Clay; Fabian Gösser; Matthew Glue; Morokot Long; Stefanie M. Rog; Pablo Sinovas; James D. Reimer (Coral Reefs, 2025)

Soil denitrification response to increased urea concentration constrains nitrous oxide emissions in a simulated cattle urine patch - Jesse C. Reimer; Melissa M. Arcand; Bobbi L. Helgason (Plant and Soil, 2024)

Tropical forcing and ENSO dominate Holocene climates in South Africa's southern Cape - Brian M. Chase; Arnoud Boom; Andrew S. Carr; Paula J. Reimer (Quaternary Science Reviews, 2024)

The British Columbia Farmers’ Market Nutrition Coupon Program Reduces Short-Term Household Food Insecurity Among Adults With Low Incomes: A Pragmatic Randomized Controlled Trial - Michelle L. Aktary; Sharlette Dunn; Tolulope Sajobi; Heather O’Hara; Peter Leblanc; Gavin R. McCormack; Stephanie Caron-Roy; Yun Yun Lee; Raylene A. Reimer; Leia M. Minaker; Kim D. Raine; Jenny Godley; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Variation in functional composition of reef fishes along a tropical‐to‐temperate gradient - Charlotte G. Clay; James D. Reimer; Brigitte Sommer; Katie M. Cook; Masaru Mizuyama; Masami Obuchi; Iori Kawamura; Hiroki Kise; Maria Beger (Journal of Biogeography, 2024)
Aims Transformation of species and functional composition on subtropical reefs are ongoing due to poleward range shifts of some tropical species, with largely unknown consequences to ecosystem functioning. Trait‐based approaches are powerful tools to quantify such changes. Here, we evaluated changes in the trait composition of coral‐associated fish assemblages along a tropical‐to‐temperate environmental gradient of ca. 1400 km in southern Japan with abundance‐weighted trait expression to assess how trait composition changes with increasing latitude. Location Ryukyu Islands and southern Pacific coast of Japan. Taxon Reef fish. Methods We tested for shifts in trait space and functional redundancy, based on five morphological, life history and behavioural traits: maximum length, pelagic larval duration, trophic level, substrate preference and reproductive mode. Our trait database was coded with two approaches, first, by attributing a single value to each trait per species, and second, by fuzzy coding that allows more than one value per trait and hence considers some intraspecific trait variation. Results We found a reduction in specialist habitat traits (coral substrate preference, nesters and herbivores) and an increase in generalist traits (predators) with increasing latitude, along with a contraction in trait space from tropical‐to‐temperate reefs. Functional redundancy declined with increasing latitude. These trends were closely linked with latitudinal gradients in temperature, along with changes in other environmental factors such as turbidity and photosynthetically active radiation. Main Conclusion Functional turnover and contractions are thus likely due to the marginal conditions for coral‐associated fishes at higher latitudes, favouring generalist species, whereas increased resources at lower latitudes favour high redundancy and niche partitioning. Accounting for intraspecific trait variation indicated the same trends but highlighted increased functional vulnerability across all sites. We show that trait complexity in coral‐associated fish communities decreases from tropical‐to‐temperate reefs, highlighting the reduced functional scope that comes with marginal environmental conditions.

Do contaminants compromise the use of recycled nutrients in organic agriculture? A review and synthesis of current knowledge on contaminant concentrations, fate in the environment and risk assessment - E.K. Bünemann; M. Reimer; E. Smolders; S.R. Smith; M. Bigalke; A. Palmqvist; K.K. Brandt; K. Möller; R. Harder; L. Hermann; B. Speiser; F. Oudshoorn; et al. (Science of The Total Environment, 2024)

Carbonate Chemistry and the Potential for Acidification in Georgia Coastal Marshes and the South Atlantic Bight, USA - Janet J. Reimer; Patricia M. Medeiros; Najid Hussain; Stephen F. Gonski; Yuan-Yaun Xu; Ting-Hsuan Huang; Wei-Jun Cai (Estuaries and Coasts, 2024)
In coastal regions and marginal bodies of water, the increase in partial pressure of carbon dioxide ( p CO 2 ) in many instances is greater than that of the open ocean due to terrestrial (river, estuarine, and wetland) influences, decreasing buffering capacity and/or increasing water temperatures. Coastal oceans receive freshwater from rivers and groundwater as well as terrestrial-derived organic matter, both of which have a direct influence on coastal carbonate chemistry. The objective of this research is to determine if coastal marshes in Georgia, USA, may be “hot-spots” for acidification due to enhanced inorganic carbon sources and if there is terrestrial influence on offshore acidification in the South Atlantic Bight (SAB). The results of this study show that dissolved inorganic carbon (DIC) and total alkalinity (TA) are elevated in the marshes compared to predictions from conservative mixing of the freshwater and oceanic end-members, with accompanying pH around 7.2 to 7.6 within the marshes and aragonite saturation states (Ω Ar ) <1. In the marshes, there is a strong relationship between the terrestrial/estuarine-derived organic and inorganic carbon and acidification. Comparisons of pH, TA, and DIC to terrestrial organic material markers, however, show that there is little influence of terrestrial-derived organic matter on shelf acidification during this period in 2014. In addition, Ω Ar increases rapidly offshore, especially in drier months (July). River stream flow during 2014 was anomalously low compared to climatological means; therefore, offshore influences from terrestrial carbon could also be decreased. The SAB shelf may not be strongly influenced by terrestrial inputs to acidification during drier than normal periods; conversely, shelf waters that are well-buffered against acidification may not play a significant role in mitigating acidification within the Georgia marshes.

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Conservation ready marine spatial planning - Julie M. Reimer; Rodolphe Devillers; Brice Trouillet; Natalie C. Ban; Tundi Agardy; Joachim Claudet (Marine Policy, 2023)

Early to Middle Holocene hydroclimate changes in the Guern El Louläilet depressions, Algerian Sahara - Nassima Yahiaoui; Bouhameur Mansour; Christos Katrantsiotis; Jan Risberg; Paula J. Reimer; M’hammed Mahboubi (Journal of Paleolimnology, 2023)

Uncertainty quantification for ecological models with random parameters - Jody R. Reimer; Frederick R. Adler; Kenneth M. Golden; Akil Narayan (Ecology Letters, 2022)
There is often considerable uncertainty in parameters in ecological models. This uncertainty can be incorporated into models by treating parameters as random variables with distributions, rather than fixed quantities. Recent advances in uncertainty quantification methods, such as polynomial chaos approaches, allow for the analysis of models with random parameters. We introduce these methods with a motivating case study of sea ice algal blooms in heterogeneous environments. We compare Monte Carlo methods with polynomial chaos techniques to help understand the dynamics of an algal bloom model with random parameters. Modelling key parameters in the algal bloom model as random variables changes the timing, intensity and overall productivity of the modelled bloom. The computational efficiency of polynomial chaos methods provides a promising avenue for the broader inclusion of parametric uncertainty in ecological models, leading to improved model predictions and synthesis between models and data.

Noise can create or erase long transient dynamics - J. R. Reimer; J. Arroyo-Esquivel; J. Jiang; H. R. Scharf; E. M. Wolkovich; K. Zhu; C. Boettiger (Theoretical Ecology, 2021)

Correction to: Two new species of threadlike blood flukes (Aporocotylidae), with a molecular revision of the genera Ankistromeces Nolan & Cribb, 2004 and Phthinomita Nolan & Cribb, 2006 - S. C. Cutmore; R. Q.-Y. Yong; J. D. Reimer; S. Shirakashi; M. J. Nolan; T. H. Cribb (Systematic Parasitology, 2021)

Two new species of threadlike blood flukes (Aporocotylidae), with a molecular revision of the genera Ankistromeces Nolan & Cribb, 2004 and Phthinomita Nolan & Cribb, 2006 - S. C. Cutmore; R. Q.-Y. Yong; J. D. Reimer; S. Shirakashi; M. J. Nolan; T. H. Cribb (Systematic Parasitology, 2021)

Insights Into Sea Turtle Population Composition Obtained With Stereo-Video Cameras in situ Across Nearshore Habitats in the Northeastern Gulf of Mexico - Tabitha Siegfried; Christopher Noren; Jackson Reimer; Matthew Ware; Mariana M. P. B. Fuentes; Susan E. Piacenza (Frontiers in Marine Science, 2021)
Population size estimates are key parameters used in assessments to evaluate and determine a species’ conservation status. Typically, sea turtle population estimates are made from nesting beach surveys which capture only hatchling and adult female life stages and can display trends opposite of the full population. As such, in-water studies are critical to improve our understanding of sea turtle population dynamics as they can target a broader range of life stages – though they are more logistically and financially challenging to execute compared to beach-based surveys. Stereo-video camera systems (SVCS) hold promise for improving in-water assessments by removing the need to physically capture individuals and instead extract 3D measurements from video footage, thereby simplifying monitoring logistics and improving safety for the animals and surveyors. To demonstrate this potential, snorkel surveys were conducted at artificial habitats in the northeastern Gulf of Mexico (neGOM) to collect size and photo-identification data on sea turtles in situ using a SVCS. Over 29.86 survey hours, 35 sea turtles were observed across three species ( Caretta caretta, Chelonia mydas , and Lepidochelys kempii ) and all neritic life stages (juvenile, sub-adult, and adult) utilizing different habitats, including artificial reefs, jetties, and fishing piers. Greens straight carapace length ranged from 28.55 to 66.96 cm ( n = 23, mean 43.07 cm ± 11.26 cm standard deviation; SD) and loggerheads ranged from 59.71 to 91.77 cm ( n = 10, mean 74.50 cm ± 11.35 cm SD), and Kemp’s ridleys ranged from 42.23 cm to 44.98 cm (mean 43.61 cm ± 1.94 cm SD). Using a linear mixed model, we found that species and habitat type were the most important predictors of sea turtle body length distribution. Overall, this case study demonstrates the potential of SVCS surveys to enhance our understanding of the population structure of sea turtle species within the neGOM and elsewhere.

An integrative approach reveals a new species of Zoantharia (Cnidaria, Anthozoa), Terrazoanthus silveirai , in the South-western Atlantic Ocean - Claudia F. Vaga; Alvaro E. Migotto; Maria E. A. Santos; Renato M. Honji; James Reimer; Marcelo V. Kitahara (Marine Biology Research, 2021)

Consensus Guidelines for Advancing Coral Holobiont Genome and Specimen Voucher Deposition - Christian R. Voolstra; Kate M. Quigley; Sarah W. Davies; John Everett Parkinson; Raquel S. Peixoto; Manuel Aranda; Andrew C. Baker; Adam R. Barno; Daniel J. Barshis; Francesca Benzoni; Victor Bonito; David G. Bourne; et al. (Frontiers in Marine Science, 2021)
Coral research is being ushered into the genomic era. To fully capitalize on the potential discoveries from this genomic revolution, the rapidly increasing number of high-quality genomes requires effective pairing with rigorous taxonomic characterizations of specimens and the contextualization of their ecological relevance. However, to date there is no formal framework that genomicists, taxonomists, and coral scientists can collectively use to systematically acquire and link these data. Spurred by the recently announced “Coral symbiosis sensitivity to environmental change hub” under the “Aquatic Symbiosis Genomics Project” - a collaboration between the Wellcome Sanger Institute and the Gordon and Betty Moore Foundation to generate gold-standard genome sequences for coral animal hosts and their associated Symbiodiniaceae microalgae (among the sequencing of many other symbiotic aquatic species) - we outline consensus guidelines to reconcile different types of data. The metaorganism nature of the coral holobiont provides a particular challenge in this context and is a key factor to consider for developing a framework to consolidate genomic, taxonomic, and ecological (meta)data. Ideally, genomic data should be accompanied by taxonomic references, i.e., skeletal vouchers as formal morphological references for corals and strain specimens in the case of microalgal and bacterial symbionts (cultured isolates). However, exhaustive taxonomic characterization of all coral holobiont member species is currently not feasible simply because we do not have a comprehensive understanding of all the organisms that constitute the coral holobiont. Nevertheless, guidelines on minimal, recommended, and ideal-case descriptions for the major coral holobiont constituents (coral animal, Symbiodiniaceae microalgae, and prokaryotes) will undoubtedly help in future referencing and will facilitate comparative studies. We hope that the guidelines outlined here, which we will adhere to as part of the Aquatic Symbiosis Genomics Project sub-hub focused on coral symbioses, will be useful to a broader community and their implementation will facilitate cross- and meta-data comparisons and analyses.

Dopamine D2 receptors in the expression and extinction of contextual and cued conditioned fear in rats - Vivian M. de Vita; Heloisa R. Zapparoli; Adriano E. Reimer; Marcus L. Brandão; Amanda R. de Oliveira (Experimental Brain Research, 2021)

Source and quantity of carbon influence its sequestration in Rostherne Mere (UK) sediment: a novel application of stepped combustion radiocarbon analysis - Evelyn M. Keaveney; Alan D. Radbourne; Suzanne McGowan; David B. Ryves; Paula J. Reimer (Journal of Paleolimnology, 2020)
We explored the roles of phytoplankton production, carbon source, and human activity on carbon accumulation in a eutrophic lake (Rostherne Mere, UK) to understand how changes in nutrient loading, algal community structure and catchment management can influence carbon sequestration in lake sediments. Water samples (dissolved inorganic, organic and particulate carbon) were analysed to investigate contemporary carbon sources. Multiple variables in a 55-cm sediment core, which represents the last ~ 90 years of accumulation, were studied to determine historical production rates of algal communities and carbon sources. Fluctuations in net primary production, inferred from sedimentary diatom abundance and high-performance liquid chromatography (HPLC) pigment methods, were linked to nutrient input from sewage treatment works (STW) in the catchment. Stepped combustion radiocarbon (SCR) measurements established that lake sediment contains between 11% (~ 1929 CE) and 69% (~ 1978 CE) recalcitrant carbon, with changes in carbon character coinciding with peaks in accumulation rate and linked to STW inputs. Catchment disturbance was identified by radiocarbon analysis, and included STW construction in the 1930s, determined using SCR analysis, and recent nearby highway construction, determined by measurements on dissolved organic carbon from the lake and outflow river. The quantity of autochthonous carbon buried was related to diatom biovolume accumulation rate (DBAR) and decreased when diatom accumulation rate and valve size declined, despite an overall increase in net carbon production. HPLC pigment analysis indicated that changes in total C deposition and diatom accumulation were related to proliferation of non-siliceous algae. HPLC results also indicated that dominance of recalcitrant carbon in sediment organic carbon was likely caused by increased deposition rather than preservation factors. The total algal accumulation rate controlled the sediment organic carbon accumulation rate, whereas DBAR was correlated to the proportion of each carbon source buried.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Acidification in the U.S. Southeast: Causes, Potential Consequences and the Role of the Southeast Ocean and Coastal Acidification Network - Emily R. Hall; Leslie Wickes; Louis E. Burnett; Geoffrey I. Scott; Debra Hernandez; Kimberly K. Yates; Leticia Barbero; Janet J. Reimer; Mohammed Baalousha; Jennifer Mintz; Wei-Jun Cai; J. Kevin Craig; et al. (Frontiers in Marine Science, 2020)

Exploring the Biodiversity of Understudied Benthic Taxa at Mesophotic and Deeper Depths: Examples From the Order Zoantharia (Anthozoa: Hexacorallia) - James Davis Reimer; Hiroki Kise; Maria E. A. Santos; Dhugal John Lindsay; Richard L. Pyle; Joshua M. Copus; Brian W. Bowen; Masanori Nonaka; Takuo Higashiji; Yehuda Benayahu (Frontiers in Marine Science, 2019)

Rare zooxanthellate Nanipora octocoral (Helioporacea) in the Gulf of Thailand - Pau Urgell Plaza; Rahul Mehrotra; Chad M. Scott; James Davis Reimer (Marine Biodiversity, 2018)

On the paraphyly of Cytaeididae and placement of Cytaeis within the suborder Filifera (Hydrozoa: Anthoathecata) - A. A. Prudkovsky; M. A. Nikitin; M. L. Berumen; Viatcheslav N. Ivanenko; J. D. Reimer (Marine Biodiversity, 2017)

Dopamine D2-like receptors modulate freezing response, but not the activation of HPA axis, during the expression of conditioned fear - Amanda R. de Oliveira; Adriano E. Reimer; Fernando M. C. V. Reis; Marcus L. Brandão (Experimental Brain Research, 2017)

Population genomics of the filarial nematode parasite Wuchereria bancrofti from mosquitoes - Scott T. Small; Lisa J. Reimer; Daniel J. Tisch; Christopher L. King; Bruce M. Christensen; Peter M. Siba; James W. Kazura; David Serre; Peter A. Zimmerman (Molecular Ecology, 2016)
Wuchereria bancrofti is a parasitic nematode and the primary cause of lymphatic filariasis – a disease specific to humans. W. bancrofti currently infects over 90 million people throughout the tropics and has been acknowledged by the world health organization as a vulnerable parasite. Current research has focused primarily on the clinical manifestations of disease and little is known about the evolutionary history of W. bancrofti . To improve upon knowledge of the evolutionary history of W. bancrofti , we whole genome sequenced 13 W. bancrofti larvae. We circumvent many of the difficulties of multiple infections by sampling larvae directly from mosquitoes that were experimentally inoculated with infected blood. To begin, we used whole genome data to reconstruct the historical population size. Our results support a history of fluctuating population sizes that can be correlated with human migration and fluctuating mosquito abundances. Next, we reconstructed the putative pedigree of W. bancrofti worms within an infection using the kinship coefficient. We deduced that there are full‐sib and half‐sib relationships residing within the same larval cohort. Through combined analysis of the mitochondrial and nuclear genomes we concluded that this is likely a results of polyandrous mating, the first time reported for W. bancrofti . Lastly, we scanned the genomes for signatures of natural selection. Annotation of putative selected regions identified proteins that may have aided in a parasitic life style or may have evolved to protect against current drug treatments. We discuss our results in the greater context of understanding the biology of an animal with a unique life history and ecology.

Transplacental Transfer of Polychlorinated Biphenyls, Polybrominated Diphenylethers, and Organochlorine Pesticides in Ringed Seals (Pusa hispida) - T. M. Brown; P. S. Ross; K. J. Reimer (Archives of Environmental Contamination and Toxicology, 2016)

A late Pleistocene–Holocene multi‐proxy record of palaeoenvironmental change from Still Bay, southern Cape Coast, South Africa - Lynne J. Quick; Andrew S. Carr; Michael E. Meadows; Arnoud Boom; Mark D. Bateman; David L. Roberts; Paula J. Reimer; Brian M. Chase (Journal of Quaternary Science, 2015)
The southern Cape is a key focus for southern African palaeoenvironmental research as it represents the transitional region between temperate westerlies and sub‐tropical rainfall sources. This study presents pollen, plant biomarker, geochemical and charcoal data preserved in the Rietvlei wetland. The bulk of the record spans the last 16 ka, but it also provides rare insights into late Marine Oxygen Isotope Stage (MIS) 3 (ca. 35–30k cal a BP). The data suggest that during the Pleistocene the development and permanence of this wetland was probably influenced by sea‐level change via control on the local water table; notably lower sea levels within MIS 2 resulted in very limited wetland productivity. The MIS 3 section provides evidence both supporting previous suggestions of relatively humid conditions, but also some indication of periodic arid phases. The Holocene record suggests clear contrasts between the early (11–7k cal a BP; relatively humid), mid‐Holocene (7–3.3k cal a BP; more arid, less productive wetland conditions) and latest Holocene (last 2k cal a BP; resurgence in both fynbos and aquatic/riparian pollen). While isolating the roles of winter/summer rainfall remains challenging, these data clarify the nature of change during key episodes in the regional palaeoenvironmental record.

Whole‐genome sequencing reveals absence of recent gene flow and separate demographic histories for Anopheles punctulatus mosquitoes in Papua New Guinea - Kyle Logue; Scott T. Small; Ernest R. Chan; Lisa Reimer; Peter M. Siba; Peter A. Zimmerman; David Serre (Molecular Ecology, 2015)
Anopheles mosquitoes are the vectors of several human diseases including malaria. In many malaria endemic areas, several species of Anopheles coexist, sometimes in the form of related sibling species that are morphologically indistinguishable. Determining the size and organization of Anopheles populations, and possible ongoing gene flow among them is important for malaria control and, in particular, for monitoring the spread of insecticide resistance alleles. However, these parameters have been difficult to evaluate in most Anopheles species due to the paucity of genetic data available. Here, we assess the extent of contemporary gene flow and historical variations in population size by sequencing and de novo assembling the genomes of wild‐caught mosquitoes from four species of the Anopheles punctulatus group of Papua New Guinea. Our analysis of more than 50 Mb of orthologous DNA sequences revealed no evidence of contemporary gene flow among these mosquitoes. In addition, investigation of the demography of two of the An. punctulatus species revealed distinct population histories. Overall, our analyses suggest that, despite their similarities in morphology, behaviour and ecology, contemporary sympatric populations of An. punctulatus are evolving independently.

Vitamin D-related gene polymorphisms, plasma 25-hydroxyvitamin D, and breast cancer risk - Laura L. Reimers; Katherine D. Crew; Patrick T. Bradshaw; Regina M. Santella; Susan E. Steck; Iryna Sirosh; Mary Beth Terry; Dawn L. Hershman; Elizabeth Shane; Serge Cremers; Elzbieta Dworakowski; Susan L. Teitelbaum; et al. (Cancer Causes & Control, 2015)

The diet of M yotis lucifugus across C anada: assessing foraging quality and diet variability - Elizabeth L. Clare; William O. C. Symondson; Hugh Broders; François Fabianek; Erin E. Fraser; Alistair MacKenzie; Andrew Boughen; Rachel Hamilton; Craig K. R. Willis; Felix Martinez‐Nuñez; Allyson K. Menzies; Kaleigh J. O. Norquay; et al. (Molecular Ecology, 2014)
Variation in prey resources influences the diet and behaviour of predators. When prey become limiting, predators may travel farther to find preferred food or adjust to existing local resources. When predators are habitat limited, local resource abundance impacts foraging success. We analysed the diet of Myotis lucifugus (little brown bats) from Nova Scotia (eastern Canada) to the Northwest Territories (north‐western Canada). This distribution includes extremes of season length and temperature and encompasses colonies on rural monoculture farms, and in urban and unmodified areas. We recognized nearly 600 distinct species of prey, of which ≈30% could be identified using reference sequence libraries. We found a higher than expected use of lepidopterans, which comprised a range of dietary richness from ≈35% early in the summer to ≈55% by late summer. Diptera were the second largest prey group consumed, representing ≈45% of dietary diversity early in the summer. We observed extreme local dietary variability and variation among seasons and years. Based on the species of insects that were consumed, we observed that two locations support prey species with extremely low pollution and acidification tolerances, suggesting that these are areas without environmental contamination. We conclude that there is significant local population variability in little brown bat diet that is likely driven by seasonal and geographical changes in insect diversity, and that this prey may be a good indicator of environment quality.

Lead, Cadmium and Zinc in Hair Samples: Relationship with Dietary Habits and Urban Environment - E. Gonzalez-Reimers; C. Martín-González; L. Galindo-Martín; M. R. Aleman-Valls; J. Velasco-Vázquez; M. Arnay-de-la-Rosa; O. Pérez-Hernández; R. Hernández Luis (Biological Trace Element Research, 2014)

Tubular Heart Valves from Decellularized Engineered Tissue - Zeeshan H. Syedain; Lee A. Meier; Jay M. Reimer; Robert T. Tranquillo (Annals of Biomedical Engineering, 2013)

Iron and Proinflammatory Cytokines in Chronic Hepatitis C Virus Infection - Javier López-Prieto; Emilio González-Reimers; M. Remedios Alemán-Valls; María José de la Vega-Prieto; Pedro Abreu-González; Ricardo Pelazas-González; Rubén Hernández-Luis; Carlos Jorge-Ripper; Francisco Santolaria-Fernández (Biological Trace Element Research, 2013)

Relative and Combined Effects of Selenium, Protein Deficiency and Ethanol on Hepatocyte Ballooning and Liver Steatosis - E. González-Reimers; M. J. Monedero-Prieto; J. M. González-Pérez; M. C. Durán-Castellón; L. Galindo-Martín; P. Abreu-González; M. J. Sánchez-Pérez; F. Santolaria-Fernández (Biological Trace Element Research, 2013)

First record of a mesophotic Pachyseris foliosa reef from Japan - T. Ohara; T. Fujii; I. Kawamura; M. Mizuyama; J. Montenegro; H. Shikiba; K. N. White; J. D. Reimer (Marine Biodiversity, 2013)

Relative and Combined Effects of Ethanol and Protein Deficiency on Bone Manganese and Copper - José M. González-Pérez; Emilio González-Reimers; María José DeLaVega-Prieto; María del Carmen Durán-Castellón; José Viña-Rodríguez; Luis Galindo-Martín; Julio Alvisa-Negrín; Francisco Santolaria-Fernández (Biological Trace Element Research, 2012)

Arsenic Speciation, Distribution, and Bioaccessibility in Shrews and Their Food - Maeve M. Moriarty; Iris Koch; Kenneth J. Reimer (Archives of Environmental Contamination and Toxicology, 2012)

Apoptosis in extracorporeal preserved inguinal fat flaps of the rat - Christian Herold; Hans O. Rennekampff; Lea Ohm; Sarah Strauß; Jörn Linkner; Kerstin Reimers; Christina Allmeling; Bernhard Vaske; Peter M. Vogt (Apoptosis, 2012)

Transactivation of lifeguard (LFG) by Akt-/LEF-1 pathway in MCF-7 and MDA-MB 231 human breast cancer cells - Vesna Bucan; Mehran Y. Adili; Claudia Y. U. Choi; Mau-Thek Eddy; Peter M. Vogt; Kerstin Reimers (Apoptosis, 2010)

High degree of conservation of the multigene tryptase locus over the past 150–200 million years of mammalian evolution - Jenny M. Reimer; Paul B. Samollow; Lars Hellman (Immunogenetics, 2010)

Relative and Combined Effects of Chronic Alcohol Consumption and HCV Infection on Serum Zinc, Copper, and Selenium - Emilio González-Reimers; M. Candelaria Martín-González; M. Remedios Alemán-Valls; María José de la Vega-Prieto; Luis Galindo-Martín; Pedro Abreu-González; Francisco Santolaria-Fernández (Biological Trace Element Research, 2009)

Learning with incomplete information in the committee machine - Urs M. Bergmann; Reimer Kühn; Ion-Olimpiu Stamatescu (Biological Cybernetics, 2009)

Non-invasive internal morphological examination of epizoic zoanthids utilizing CT scanners - J. D. Reimer; F. Sinniger; M. Nonaka; S. Uchida (Coral Reefs, 2009)

Allelic variation at Psy1-A1 and association with yellow pigment in durum wheat grain - A. Singh; S. Reimer; C. J. Pozniak; F. R. Clarke; J. M. Clarke; R. E. Knox; A. K. Singh (Theoretical and Applied Genetics, 2009)

Morphological and molecular characterization of a new genus and new species of parazoanthid (Anthozoa: Hexacorallia: Zoantharia) associated with Japanese Red Coral - J. D. Reimer; M. Nonaka; F. Sinniger; F. Iwase (Coral Reefs, 2008)

Long-term ice sheet–climate interactions under anthropogenic greenhouse forcing simulated with a complex Earth System Model - Miren Vizcaíno; Uwe Mikolajewicz; Matthias Gröger; Ernst Maier-Reimer; Guy Schurgers; Arne M. E. Winguth (Climate Dynamics, 2008)

Prognostic Value of Serum Selenium Levels in Alcoholics - Emilio González-Reimers; Luis Galindo-Martín; Francisco Santolaria-Fernández; María José Sánchez-Pérez; Julio Alvisa-Negrín; Elena García-Valdecasas-Campelo; Jose María González-Pérez; M. Candelaria Martín-González (Biological Trace Element Research, 2008)

Evolutionary origin of the segmental duplication encompassing the wheat GLU-B1 locus encoding the overexpressed Bx7 (Bx7OE) high molecular weight glutenin subunit - Raja Ragupathy; Hamid A. Naeem; Elsa Reimer; Odean M. Lukow; Harry D. Sapirstein; Sylvie Cloutier (Theoretical and Applied Genetics, 2008)

Long-term effects of anthropogenic CO2 emissions simulated with a complex earth system model - Uwe Mikolajewicz; Matthias Gröger; Ernst Maier-Reimer; Guy Schurgers; Miren Vizcaíno; Arne M. E. Winguth (Climate Dynamics, 2007)

Evidence for subdivision within the M molecular form of Anopheles gambiae - M. A. SLOTMAN; F. TRIPET; A. J. CORNEL; C. R. MENESES; Y. LEE; L. J. REIMER; T. C. THIEMANN; E. FONDJO; A. FOFANA; S. F. TRAORÉ; G. C. LANZARO (Molecular Ecology, 2007)
The principal vector of malaria in sub‐Saharan Africa, Anopheles gambiae is subdivided into two molecular forms M and S. Additionally, several chromosomal forms, characterized by the presence of various inversion polymorphisms, have been described. The molecular forms M and S each contain several chromosomal forms, including the Savanna, Mopti and Forest forms. The M and S molecular forms are now considered to be the reproductive units within A. gambiae and it has recently been argued that a low recombination rate in the centromeric region of the X chromosome has facilitated isolation between these forms. The status of the chromosomal forms remains unclear however. Therefore, we studied genetic differentiation between Savanna S, Forest S, Forest M and Mopti M populations using microsatellites. Genetic differentiation between Savanna S and Forest S populations is very low ( F ST = 0.0053 ± 0.0049), even across large distances. In comparison, the Mopti M and Forest M populations show a relatively high degree of genetic differentiation ( F ST = 0.0406 ± 0.0054) indicating that the M molecular form may not be a single entity, but could be subdivided into at least two distinct chromosomal forms. Previously it was proposed that inversions have played a role in the origin of species within the A. gambiae complex. We argue that a possible subdivision within the M molecular form could be understood through this process, with the acquisition of inversions leading to the expansion of the M molecular form into new habitat, dividing it into two distinct chromosomal forms.

Identification of the non-specific cytotoxic cell receptor protein 1 (NCCRP1) in regenerating axolotl limbs - Kerstin Reimers; Mehtap Abu Qarn; Christina Allmeling; Vesna Bucan; Peter M. Vogt (Journal of Comparative Physiology B, 2006)

Expansion of the mast cell chymase locus over the past 200 million years of mammalian evolution - Maike Gallwitz; Jenny M. Reimer; Lars Hellman (Immunogenetics, 2006)

Comparison of Five Eulerian Air Pollution Forecasting Systems for the Summer of 1999 Using the German Ozone Monitoring Data - Stefan Tilmes; JØrgen Brandt; Frode FlatØy; Robert Bergström; Johannes Flemming; Joakim Langner; Jesper H. Christensen; Lise M. Frohn; Øystein Hov; Ingo Jacobsen; Eberthard Reimer; Rainer Stern; et al. (Journal of Atmospheric Chemistry, 2002)

Relative and combined effects of ethanol and protein deficiency on strontium and barium bone content and fecal and urinary excretion - E. Gonzalez-Reimers; F. Rodriguez-Moreno; A. Martinez-Riera; A. Mas-Pascual; E. Delgado-Ureta; L. Galindo-Martin; M. Arnay-de La Rosa; F. Santolaria-Fernandez (Biological Trace Element Research, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Bone trace element pattern in an 18th century population sample of tenerife (Canary islands) - M. Arnay-de-la-Rosa; E. Gonzalez-Reimers; J. Velasco-Vazquez; N. Barros-Lopez; L. Galindo-Martin (Biological Trace Element Research, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Immunological characterization of heterochromatin protein p25β autoantibodies and relationship with centromere autoantibodies and pulmonary fibrosis in systemic scleroderma - Kiyoshi Furuta; Bernhard Hildebrandt; Sayako Matsuoka; Kendo Kiyosawa; Georg Reimer; Christoph Luderschmidt; Edward K. L. Chan; E. M. Tan (Journal of Molecular Medicine, 1997)

Paleodietary analysis on the prehistoric population of El Hierro (Canary Islands) - J. Velasco-V⟹quez; M. Armay-de-la-Rosa; E. González-Reimers; O. Hernández-Torres (Biological Trace Element Research, 1997)

Unbiased cocaine conditioned place preferences (CPP) obscures conditioned locomotion, and nimodipine blockade of cocaine CPP is due to conditioned place aversions - M. T. Martin-Iverson; Allan R. Reimer; Sudheer Sharma (Psychopharmacology, 1997)